Statistical analysis of scanning fluorescence correlation spectroscopy data differentiates free from hindered diffusion - Schneider, F; Waithe, D; Lagerholm, B; Shrestha, D; Sezgin, E; Eggeling, C; Fritzsche, M (American Chemical Society, 2018)
Cells rely on versatile diffusion dynamics in their plasma membrane. Quantification of this often heterogeneous diffusion is essential to the understanding of cell regulation and function. Yet such measurements remain a major challenge in cell biology, usually due to low sampling throughput, a necessity for dedicated equipment, sophisticated fluorescent label strategies, and limited sensitivity. Here, we introduce a robust, broadly-applicable statistical analysis pipeline for large scanning-fluorescence-correlation-spectroscopy data sets, which uncovers the nanoscale heterogeneity of the plasma membrane in living cells by differentiating free from hindered diffusion modes of fluorescent lipid and protein analogues.